Distinct Spatial Relationship of the Interleukin‐9 Receptor with Interleukin‐2 Receptor and Major Histocompatibility Complex Glycoproteins in Human T Lymphoma Cells. Issue 18 (8th October 2014) - Nizsalóczki, Enikő; Csomós, István; Nagy, Péter; Fazekas, Zsolt; Goldman, Carolyn K.; Waldmann, Thomas A.; Damjanovich, Sándor; Vámosi, György; Mátyus, László; Bodnár, Andrea
Abstract The interleukin‐9 receptor (IL‐9R) consists of an α subunit and a γc chain that are shared with other cytokine receptors, including interleukin‐2 receptor (IL‐2R), an important regulator of T cells. We previously showed that IL‐2R is expressed in common clusters with major histocompatibility complex (MHC) glycoproteins in lipid rafts of human T lymphoma cells, which raised the question about what the relationship between clusters of IL‐2R/MHC and IL‐9R is. Confocal microscopy colocalization and fluorescence resonance energy transfer experiments capable of detecting membrane protein organization at different size scales revealed nonrandom association of IL‐9R with IL‐2R/MHC clusters at the surface of human T lymphoma cells. Accommodation of IL‐9Rα in membrane areas segregated from the IL‐2R/MHC domains was also detected. The bipartite nature of IL‐9R distribution was mirrored by signal transducer and activator of transcription (STAT) activation results. Our data indicate that co‐compartmentalization with MHC glycoproteins is a general property of γc receptors. Distribution of receptor chains between different membrane domains may regulate their function.